PENGELOLAAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN PRESTASI UJIAN AKHIR SEKOLAH(UAS) DI SD NEGERI 33 KALUMBUK KOTA PADANG - Hana Khairi Afriyanli (Universitas Negeri Padang, 2019)
Education must have a clear vision and mission to produce quality output and be able to be optimally oriented today. In order to achieve the desires of educational institutions that can produce quality output, the quality and results of educational institutions need to be organized within the institution, in which there must be definite management. In conducting observations carried out using a descriptive qualitative approach. The data collection method used is interview. The intended results are the results of the UAS in 2018 which are expected to be above SKL determined by schools and by 2020 and can reach an average of 7.5. The results of the UAS include a minimum score and an average of 3 subjects (Indonesian Language, Mathematics, Science) with a target of 100% graduation rate and top 5 ranking at the sub-district level. The UAS Value target for 2020.